Inconsistent diagnosis of acute malnutrition by weight-for-height and mid-upper arm circumference: Contributors in 16 cross-sectional surveys from South Sudan, the Philippines, Chad, and Bangladesh - Roberfroid, Dominique; Huybregts, Lieven; Lachat, Carl; Vrijens, France; Kolsteren, Patrick; Guesdon, Benjamin (BioMed Central, 2015)
The two anthropometric indicators of acute malnutrition in children under 5 years, i.e. a Mid-Upper Arm Circumference < 125 mm (MUAC125) or a Weight-for-Height Z-score<−2 (WHZ−2), correlate poorly. We aimed at assessing the contribution of age, sex, stunting (Height-for-Age HAZ<−2), and low sitting-standing height ratio Z-score (SSRZ in the 1st tertile of the study population, called hereafter 'longer legs') to this diagnosis discrepancy. Data from 16 cross-sectional nutritional surveys carried out by Action Against Hunger International in South Sudan, the Philippines, Chad, and Bangladesh fed multilevel, multivariate regression models, with either WHZ−2 or MUAC125 as the dependent variable and age, sex, stunting, and 'longer legs' as the independent ones. We also compared how the performance of MUAC125 and WHZ−2 to detect slim children, i.e. children with a low Weight-for-Age (WAZ<−2) but no linear growth retardation (HAZ≥−2), was modified by the contributors. Overall 23.1 % of the 14,409 children were identified as acutely malnourished by either WHZ−2 or MUAC125, but only 28.5 % of those (949/3,328) were identified by both indicators. Being stunted (+17.8 %; 95 % CI: 14.8 %; 22.8 %), being a female (+16.5 %; 95 % CI: 13.5 %; 19.5 %) and being younger than 24 months (+33.6 %; 95 % CI: 30.4 %; 36.7 %) were factors strongly associated with being detected as malnourished by MUAC125 and not by WHZ−2, whereas having 'longer legs' moderately increased the diagnosis by WHZ−2 (+4.2 %; 95 % CI: 0.7 %; 7.6 %). The sensitivity to detect slim children by MUAC125 was 31.0 % (95 % CI: 26.8 %; 35.2 %) whereas it was 70.6 % (95 % CI: 65.4 %; 75.9 %) for WHZ−2. The sensitivity of MUAC125 was particularly affected by age (57.4 % vs. 18.1 % in children aged < 24 months vs. ≥ 24 months). Specificity was high for both indicators. MUAC125 should not be used as a stand-alone criterion of acute malnutrition given its strong association with age, sex and stunting, and its low sensitivity to detect slim children. Having 'longer legs' moderately increases the diagnosis of acute malnutrition by WHZ−2. Prospective studies are urgently needed to elucidate the clinical and physiological outcomes of the various anthropometric indicators of malnutrition.